A novel ICK mutation causes ciliary disruption and lethal endocrine-cerebro-osteodysplasia syndrome. Issue 1 (December 2016) - Oud, Machteld; Bonnard, Carine; Mans, Dorus; Altunoglu, Umut; Tohari, Sumanty; Ng, Alvin; Eskin, Ascia; Lee, Hane; Rupar, C.; Wagenaar, Nathalie; Wu, Ka; Lahiry, Piya; et al.
Abstract Background Endocrine-cerebro-osteodysplasia (ECO) syndrome [MIM:612651] caused by a recessive mutation (p.R272Q) in Intestinal cell kinase (ICK) shows significant clinical overlap with ciliary disorders. Similarities are strongest between ECO syndrome, the Majewski and Mohr-Majewski short-rib thoracic dysplasia (SRTD) with polydactyly syndromes, and hydrolethalus syndrome. In this study, we present a novel homozygousICK mutation in a fetus with ECO syndrome and compare the effect of this mutation with the previously reported ICK variant on ciliogenesis and cilium morphology. Results Through homozygosity mapping and whole-exome sequencing, we identified a second variant (c.358G > T; p.G120C) inICK in a Turkish fetus presenting with ECO syndrome. In vitro studies of wild-type and mutant mRFP-ICK (p.G120C and p.R272Q) revealed that, in contrast to the wild-type protein that localizes along the ciliary axoneme and/or is present in the ciliary base, mutant proteins rather enrich in the ciliary tip. In addition, immunocytochemistry revealed a decreased number of cilia in ICK p.R272Q-affected cells. Conclusions Through identification of a novelICK mutation, we confirm that disruption ofICK causes ECO syndrome, which clinically overlaps with the spectrum of ciliopathies. Expression of ICK-mutated proteins result in an abnormal ciliary localization compared to wild-type protein. Primary fibroblasts derived from an individual with ECO syndrome display ciliogenesis defects. In aggregate, our findings are consistent with recent reports that show that ICK regulates ciliary biology in vitro and in mice, confirming that ECO syndrome is a severe ciliopathy.